2018
DOI: 10.24326/asphc.2018.2.9
|View full text |Cite
|
Sign up to set email alerts
|

IMPROVEMENT OF SILYMARIN CONTENT IN CELL CULTURES OF Silybum marianum BY COPPER SULPHATE ELICITOR

Abstract: Silybum marianum L. (Milk thistle) extracts are the main source of silymarin that is a mixture of various flavonolignan (silybin (silibinin), silydianin and silychristin). Silymarin of milk thistle has a hepatoprotective activity for liver cirrhosis and chronic inflammatory. Silybum marianum regeneration from hypocotyl explants and evaluation of their callogenesis, growth and total flavolignan (silymarin) upon copper sulphate (as abiotic elicitor) elicitation was targeted. Copper sulphate (CuSO 4) was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…Seeds of S. marianum were cultured on half-strength MS medium supplemented with 3% (w/v) sucrose and solidified with 3 g/L phytagel. The use of half-strength MS medium for seed germination gave comparable results with those of Elsharnouby and Hassan (2018), who reported that it was better than the full-strength medium, due to the osmotic pressure of the latter. Also, the germination process was enhanced by incubating the seeds in complete darkness until seedling formation.…”
Section: Seed Germinationsupporting
confidence: 67%
See 2 more Smart Citations
“…Seeds of S. marianum were cultured on half-strength MS medium supplemented with 3% (w/v) sucrose and solidified with 3 g/L phytagel. The use of half-strength MS medium for seed germination gave comparable results with those of Elsharnouby and Hassan (2018), who reported that it was better than the full-strength medium, due to the osmotic pressure of the latter. Also, the germination process was enhanced by incubating the seeds in complete darkness until seedling formation.…”
Section: Seed Germinationsupporting
confidence: 67%
“…Also, the germination process was enhanced by incubating the seeds in complete darkness until seedling formation. These results are corroborated by Elsharnouby and Hassan (2018), who stated that light was unnecessary in the germination period of S. marianum seeds due to its inhibitory effect ( Khan et al, 2013).…”
Section: Seed Germinationsupporting
confidence: 56%
See 1 more Smart Citation
“…Adding CuSO 4 to the culture media of S. marianum calluses has increased silymarin content by four to five folds relative to the control (Elsharnouby & Hassan, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…In fact, the presence of heavy metal ions trigger changes in metabolic activities of plants and affect the production of photosynthetic pigments, sugars, proteins, and non‐protein thiols Thakur et al, 2019). Adding CuSO 4 to the culture media of S. marianum calluses has increased silymarin content by four to five folds relative to the control (Elsharnouby & Hassan, 2018).…”
Section: Resultsmentioning
confidence: 99%